AFKAR AMIN AL-KHULI FI TA’LIM AL-BALAGHAH AL-‘ARABIYAH - Mohammad Izdiyan Muttaqin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This research discussed the ideas of Amin al-Khuli in the teaching of Arabic literature or Balaghah. The name Amin al-Khuli is popular as the reformer of Balaghah. This research was a qualitative research. This research used two books of Amin al-Khuli, i.e., Manahij Tajdid and Fannul Qaul. The result of this research concluded that Amin al-Khuli emphasized two important goals of teaching Balaghah, i.e., the practical and artistic goals. He did not consider the importance of religious goals of Balaghah to understand the Qur’an. In terms of contents, he denied the classification of Balaghah into Ma’ani, Bayan, and Badi’; instead, he changed it into kalimat (words), jumal (sentences), fiqrah (paragraph), and shuwar ta’biriyyah (kinds of expressions). The research emphasized the importance of conducting further research to create a better textbook of Balaghah based on Amin Khuli’s ideas.